Successful management of haemoglobinuria in a buffalo - Thounaojam, Richard; Joshi, Vivek; Naveen, Nagella; Mondal, D. B. (Indian Journal of Veterinary Medicine, 2024)
Nutritional hemoglobinuria is a disease of high-yielding buffaloes due to hypophosphatemia or cruciferous plant poisoning, causing intravascular haemolysis and haemoglobinuria. A 7-year-old non-descript multiparous buffalo in advanced pregnancy was presented to Referral Veterinary Polyclinic of ICAR-Indian Veterinary Research Institute, Izatnagar with a history of coffee-coloured urine and anorexia for a period of two days. It was reported that buffalo had ingested radish shoots about 7 datys earlier. Clinical examination revealed dullness with pale mucus membranes and reduced rumination. Haematobiochemical examination revealed reduced levels of haemoglobin, PCV, marked neutrophilia, hypophosphatemia, elevated BUN and hypoproteinemia. The buffalo was treated with sodium acid phosphate (50 ml IV q12h on 3 occasions), ascorbic acid (5 mg/kg IV q24h for 1-week), vitamin B-complex and iron sorbitol folic acid complex. The buffalo recovered uneventfully following therapy.